Family support in the elderly with type 2 diabetes mellitus: A literature review - KK, Indra Frana Jaya; Putri, Amelia; Wijaya, Brahma Putra; Zulkarnaen, Ahmad (Science Center Group, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic disease with an increasing prevalence among the elderly and requires long-term management to prevent complications. Effective diabetes management depends not only on medical treatment but also on consistent self-care behaviors and medication adherence, in which family support plays an essential role. Objective: This study aimed to examine the role of family support in the management of Type 2 Diabetes Mellitus among elderly patients through a literature review. Methods: A literature review was conducted by analyzing relevant articles published in international peer-reviewed journals focusing on family support and diabetes management in elderly populations. Articles were selected based on predefined inclusion criteria related to study population, family support dimensions, and diabetes management outcomes. The selected literature was systematically reviewed and synthesized to identify patterns and key findings regarding the role of family support. Results: The findings demonstrated that family support, including emotional, informational, and instrumental support, was associated with improved glycemic control, better medication adherence, enhanced self-care behaviors, and improved quality of life among elderly patients with T2DM. However, several barriers were identified, such as limited family knowledge about diabetes management and restricted access to healthcare services, which may reduce the effectiveness of family support. Conclusion: Family support plays a critical role in the effective management of Type 2 Diabetes Mellitus in the elderly. Strengthening family-centered health education and integrating family involvement into long-term diabetes care models are recommended to optimize clinical outcomes and improve the overall quality of life of elderly patients with T2DM.